Reprogramming the tumor-immune landscape via nanomaterial-induced immunogenic cell death: a mini review - Meng, Xiangwei; Che, Chunqing; Yi, Yingjie; Qu, Xiaoyang (Frontiers in Bioengineering and Biotechnology, 2025)
Nanomaterial-induced immunogenic cell death (ICD) represents a transformative approach to overcoming limitations of conventional cancer immunotherapies. Unlike traditional methods hindered by systemic toxicity and inadequate targeting, nanomaterials precisely deliver therapeutic agents and effectively modulate tumor microenvironmental factors, including hypoxia, acidity, and redox imbalance. By triggering ICD through mechanisms such as reactive oxygen species generation, tumor acidity neutralization, and hypoxia alleviation, nanomaterials facilitate potent anti-tumor immune responses, enhance dendritic cell activation, and promote cytotoxic T lymphocyte recruitment. Additionally, integrating nanomaterial-induced ICD with established immunotherapies like checkpoint inhibitors and CAR-T cells has shown promising preclinical synergy, enabling robust and lasting antitumor immunity. Despite significant translational challenges related to safety, standardization, and tumor heterogeneity, continued advances in multifunctional nanoplatform development and personalized therapeutic strategies hold substantial promise for improving cancer treatment outcomes.